Yoğun Bakım Seçilmiş Semptom Bulguların Yönetimi (3. BASKI) - Çakır, Melike; Ulugöl, Halim; Toraman, Fevzi; Ilgaz Koçyiğit, Özgen; Öztürk Altuncevahir, İlayda and Akyüz Özdemir, Ferda and Toygar, İsmail and Çınar, Fadime and Çakmak, Mehmet Aziz and Özer, Nadiye and Koç Aslan, Saliha and Parlak, Göknur and Yava, Ayla and Koyuncu, Aynur and Akgün, Ali and Ateş, Sebahat and Çelik, Sevim and Altıntaş, Sibel and Kaplan Afacan, Zeynep and Özyürek, Pakize and Yavuz Van Giersbergen, Meryem and Sivaslı, Alev and Çiğdem, Zerrin and Aygin, Dilek and Demir Korkmaz, Fatma and Taşkın Yılmaz, Feride and Gökçe Eskin, Serap and Boyraz Özkavak, Sakine and Gezer, Nurdan and Çinar, Halise and Bilik, Özlem and Özkan, Sultan and Arslan, Ezgi and Gedik Çelik, Selda and Bayraktar, Nurhan and Çilingir, Dilek and Ören, Besey and Can, Gülbeyaz and Karakoç Kumsar, Azime and Zengin, Neriman and Bayındır Çevik, Ayfer and Sert, Havva and Çil Akıncı, Ayşe and Yalın, Hayat and Erdoğan, Zeynep and Yıldız, Hicran and Katran, Hamdiye Banu and Teber, Sena and Polat, Selda and Ataman Yıldız, Gamze and Kulaksızoğlu, Havvane and Çetinkaya, Melis Merve and Kıvanç, Özlem (Academician Publishing Book DOI Portal, 2024)
-